ASSESSMENT OF SELF-MEDICATION PRACTICES AMONG NON-MEDICAL COLLEGE STUDENTS - DR. ANURADHA DUBEY,; DR. HANMANT S. AMANE,; DR. SHILPA KAORE, (International Journal of Pharma and Bio Sciences, 2014)
The aim of this study was to evaluate prevalence, knowledge and attitude towards self-medication practices among non-medical students for which a cross sectional survey was conducted in some non-medical colleges in Bhopal. After explaining the purpose of the study and taking informed consent, a questionnaire was provided to the students. We divided the questionnaire into three parameters, in first parameter, demographic characteristics of the students were noted, in another, the prevalence and practice of self-medication were noted, whereas the last section assessed the attitude of students towards self-medication. We collected the details about the medication utilized, ailments for which the drugs were consumed and reasons for self-medication. Accorging to the results of this study, the self-medication practices were very common among non-medical students in Bhopal. Further interventional studies are required to educate people and curb the self-medication practices in students as well as the general population.